Xanthogranulomatous inflammation involving the gallbladder, bile duct, and pancreas: a case report - Zhang, Jinchang; Lin, Haomin; Li, Xujia; Wang, Piao; Yang, Xiaoli; Li, Bo; Guo, Qinxi; Su, Song (Frontiers in Oncology, 2023)
Xanthogranulomatous inflammation (XGI) is a rare, benign condition that can affect several organs, including the gallbladder, kidney, skin, gastrointestinal tract, lymph nodes, and soft tissues. It is often misdiagnosed as a malignancy. In this report, we present the case of a 79-year-old male who presented with persistent jaundice for 11 months. Computed tomography and magnetic resonance imaging revealed pancreatic head enlargement, gallbladder thickening, and common bile duct thickening, leading to a preoperative diagnosis of malignant neoplasm of the pancreatic head. During surgery, dense adhesions were found around the portal vein, suggestive of mass invasion. To relieve obstruction, choledochojejunostomy was performed. Postoperative pathological examination revealed xanthogranulomatous cholecystitis (XGCc), xanthogranulomatous cholangitis (XGCg), and xanthogranulomatous pancreatitis (XGP). XGI affecting the bile ducts and pancreas is extremely rare, and there are no reported cases of simultaneous involvement of the gallbladder, bile duct, and pancreas by XGI. This study provides valuable insight into the differential diagnosis of XGI by presenting the imaging features of XGI patients.